Tarling Music Digitalization and Transformation in Network Society Era - Imawan, Khaerudin; Sari, Tribuana (KnE Social Sciences, 2019)
Since its birth in the 1930s tarling music recordings have undergone many changes, depending on technological developments. Starting from recording types of vinyl, cassette tapes to Compact Disk technology. In fact, along with digital technology the production of tarling music recordings can be done indie in the form of document files. The process of digitizing tarling music production is also inseparable from the weak regulation of copyright, so that the results of massive tarling music production can spread through cyberspace. This qualitative study uses the Historical Materialism paradigm by analyzing how Tarling’s music undergoes transformation, distribution and consumption. As a result, the tactic of digitalization has contributed greatly to the changing transformation of Tarling’s music. The phenomenon of network society also forces the role of the agents behind Tarling’s music to contest by using digital production and marketing strategies through Youtube accounts that are disseminated through social media channels. Digital technology has revived tarling music, which was originally a classic-music that is almost extinct, is now able to stand side by side and even collaborate with various other popular music. Keywords: Tarling music, digital distribution, network community.